Perlindungan Konsumen dalam Jual Beli Perumahan Secara Kredit di Perumahan “Griya Kademangan Indah” Demangan Siman Ponorogo Perspektif Hukum Islam - Mohamad Faisal Aulia (Journal of Sharia and Legal Science, 2023)
This study aims to determine consumer protection in buying and selling housing on credit in housing "Griya Kademangan Indah" Demangan Siman Ponorogo Perspective of Islamic Law. In this study used a descriptive type of research. The data used in this study are secondary data by studying and analyzing legal materials and Tertiary Legal Materials, namely legal materials that provide instructions and explanations to primary and secondary legal materials, namely: legal dictionaries and Indonesian dictionaries. In this case, the researcher examines and analyzes related to legal protection in buying and selling housing on credit in Griya Kademangan Indah Demangan Siman Ponorogo housing Perspective of Islamic Law. The results of the research in this writing are: In this housing using the concept of buying and selling shari'ah and the laws and contracts used are different, some use islamic law contracts and some also use contracts in laws. The housing provided is also in the form of ready stock or ready-made materials, most likely the buyer feels satisfaction in choosing the house he will live in, because the principle is consensual the buyer offers according to what the buyer expects, because the legal condition for buying and selling is mutual favor. In the transaction of buying and selling housing in housing "Griya Kademangan Indah" explained that in buying and selling housing this carries the concept of no usury, it can be seen in the practice of implementation that they do not involve third parties, namely conventional banks or shari'a banks in their transactions, on the grounds that banks still have elements of usury. So in payments made by consumers to housing owners, it can be directly to the housing owner, it can be content or cash and can also be paid in installments directly to the housing owner in accordance with the agreed agreement because it does not contain an element of usury in it